Cross-country skiing: Special power+endurance HIIT-testing - Shishkina, A.; Tarbeeva, N.; Tarbeeva, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: In cross-country skiing huge variety of skiing landscape and snow surface temperature and the lack of standard testing conditions cause the difficulties for objective diagnostics of special skiing physical workability, strength and endurance. Therefore, the aim of this study was to evaluate the diagnostic possibilities of high-intensity interval training (HIIT) for the assessment of skiers special readiness. Methods: For testing under training conditions Ercolina Upper Body Power Cross-Country Ski Poling Simulator with power meter option that provides digital power readings (distance in meters, speed in km/h, power for each push in watts, etc) was used. After warming-up trained athletes performed diagonal (single) poling using HIITraining named Tabata Protocol consisting of eight sets of 20-second maximal intensity work interval with 10 seconds of passive recovery between each bout. Heart rate monitoring and blood lactate responses at rest, after last work interval and in recovery were under consideration. Results: The authors of Tabata Protocol Dr. Izumi Tabata and the researchers from the National Institute of Fitness and Sports, Japan suggested to monitor Tabata account, that is the lowest result of 8 intervals. We suggest to analyze the best result among 8 distance intervals, the lowest one, their delta, amount of 8 results (total distance) as well as the speed of results decreasing. For example, the following distance results were obtained: 149-139-138-123-120-118-113-114. Discussion: The longest distance (149) corresponds to the anaerobic capacity and serves a measure of speed and power abilities. Distance difference (delta between the longest and shortest distances, Ä=36) accepts as a criterion of the development of speed endurance. Total distance (1014) characterizes the special endurance and anaerobic glycolytic potential of performance muscle groups of skiers The value of the total distance are affected by speed and power abilities levels, long anaerobic endurance and the rate of results decreasing determined from which cycle and how dramatically the results decreasing occurs. It mainly depends on an athlete ability to rapid recovery during 10 seconds of rest. Thus, Tabata interval training can be used to control the level of readiness of skiers, allow to determine the athletes` weaknesses and to design the training program for them. Regular including HIIT test in training process provides necessary information for managing an athlete preparation and also acts as effective exhaustive intermittent workout. Test may be fulfilled with a variety of training facilities as well as be informative in other sport.